(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The aim of this study is to minimize the energy consumption in sensors in wireless body area networks by using ITHE protocol (Improved Temperature Heterogeneity Energy) compared with THE (Temperature Heterogeneity Energy) protocol. Materials and Methods: In this research uninterrupted communication with minimized energy consumption is achieved using Clustering mechanism with a mobile patient monitoring system in WBAN. The energy consumption is achieved using efficient coordinator node (CN) and Serving coordinator node (SCN) selection using various parameters such as Innovative node position,distance and residual energy of the sensor nodes.The sample size of each group is 20 (n=20) collected by varying the number of rounds and it was calculated by calculator.Net with pre-test power of 80% (G-power). Result: Simulation results show that ITHE protocol has performed better than THE Protocol in terms of throughput and energy consumption respectively. The proposed ITHE protocol achieved (2.3%) higher Throughput and (19%) lower energy consumption compared with THE protocol. The sample t-test shows that there is a significant difference in ITHE and THE values in terms of energy consumption and throughput (p<0.05). Conclusion: Depending on the experimental results and independent statistical T-test shows that proposed ITHEprotocol has achieved higher performance when compared to THE protocol.